PEMERINTAH DAN MASYARAKAT ( KEBIJAKAN LABEL PADA BARANG DI KOTA PEKANBARU TAHUN 2011-2013) - Husnul Khotimah; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Labeling policies on these items interesting to study because of widespread circulation of goods which are not labeled in accordance with the provisions established in order to safeguard the rights - the rights of consumers of action - fraudulent acts committed by manufacturers and traders who are not in accordance with the provisions.This study used a qualitative method and conducted in the city of Pekanbaru. This study uses informants as sources of information objects that aims to achieve mastery in getting information. Data used in this study are primary data and secondary data obtained through direct observation and interviews with informants. Analysis of the data in a descriptive study conducted by describing the data in a systematic and objective so as to produce factual information, current, and accurate.Based on the results of this research is policy implementation labeling obligations is considered quite able to solve the problems that have been experienced by consumers as users of the goods that have been produced by the manufacturer. It can be seen from the purpose of this policy made. Department of Industry and Trade as actors implementing and controlling labeling policy periodically monitoring and sustainable in terms of overseeing the goods are already in the market, but have not been able to decide this matter, which had found in the field. This is because the Department of Industry and Trade as the local government which is an extension of the central government was not able to do much because the highest authority in the tackle and make decisions in a policy on this issue is at the Ministry of Industry and Trade.Keyword: Policy, Label, Pekanbaru.